POLA ASUH ORANG TUA DALAM PENDIDIKAN KARAKTER ANAK USIA DINI - andini dwi arumsari (MOTORIC, 2021)
Character building of children is carried out from early childhood. Family becomes the first environment in the process of children's character education. Parental compassion is one of the main factors in educating and shaping children's character. There are three types of parenting style, namely permissive parenting, authoritarian parenting, and democratic parenting. Children who are educated using permissive parenting will become stubborn, cling to their opinions and appear to be indifferent to others. Authoritarian parenting shapes children into children who have character who tend not to be able to solve their own problems, always need help and are not independent. Meanwhile, democratic parenting forms children to be independent, and able to control themselves, have high self-confidence, be able to socialize well in their environment, are able to overcome the problems they have, are interested in new things, are cooperative with older people, become children who obey and obey parental orders, and have high achievement motivation. However, what happens in society is that parents do not only use one parenting style in educating their children Keywords: Character education, parenting, early childhood